Pengaruh Mobile Legends Terhadap Minat dan Semangat Belajar Mahasiswa - Anggraeni, Vidiya; Setyawan, Agung; Zuhria, Zirli Amanatus (Program Studi Tadris IPS Institut Agama Islam Negeri (IAIN) Parepare, 2022)
This study aims to determine the effect of mobile legends games on student enthusiasm and interest in learning. The author raises this theme because of the rise of mobile legends games among students, with active users in Indonesia of approximately 34 million users. This study uses a quantitative method. The results of the research carried out obtained an average variable point for the level of enthusiasm and interest in learning among users of the mobile legends game for FIP 2021 students, namely 17.3 in the interval 16 - 19.9 and are in fewer qualifications. The average variable points that often delay assignments because playing mobile legends is 34.6 at intervals 31-36 and is in sufficient qualification. And from the results of the simple linear regression test it shows a value of Sig 0.002 <0.005 and Sig 0.000 <0.005 so it can be concluded that the variable delay in completing assignments and enthusiasm and interest in learning has no effect on the variable use of the mobile legends of FIP 2021 students.